Algerian university professors' use of Arab news channels and their gratification: - A study of a sample of Algerian university professors – - Benguit , djoudi; merzougui, bader addin (Journal of Social Sciences and Humanities, 2021)
Arab news channels constitute a large part of the satellite channels received by the Arab viewer, including the Algerian viewer, and among them are the university professors. this study will shed light the use of the Algerian university professors of the Arab news channels and the benefits they achieved from its use, this topic is mainly one of the current topics that deserve study and research, moreover; it is discussed according to the introduction of uses and gratifications, and the questionnaire form with a sample of (325) single Algerian university professors ,for this purpose, three Algerian universities were intentionally chosen ,including the universities of Laghouat, , Ghardaia and Ouargla with a 10 percentage from each university, this study also relied on the descriptive approach, focused on studying the habits and patterns of Algerian university professors' use of the news channels, their satisfactions, and the type The news channels that university professors prefer to follow either News channels of Arab countries or foreign channels speaking in the Arabic language. The results of the study show that a large percentage of university professors spend less than an hour a day watching Arab news channels, whereas , another large percentage spend between an hour to three hours a day, and the majority follow Arab news channels at night. The later also prefer to follow the Arab news channels of Arab countries mainly more than foreign news channels that speak Arabic for a deeper view of daily events with a greater percentage than other reports.